How Pointing is Integrated into Language: Evidence From Speakers and Signers - Cooperrider, Kensy; Fenlon, Jordan; Keane, Jonathan; Brentari, Diane; Goldin-Meadow, Susan (Frontiers in Communication, 2021)
When people speak or sign, they not only describe using words but also depict and indicate. How are these different methods of communication integrated? Here, we focus on pointing and, in particular, on commonalities and differences in how pointing is integrated into language by speakers and signers. One aspect of this integration is semantic—how pointing is integrated with the meaning conveyed by the surrounding language. Another aspect is structural—how pointing as a manual signal is integrated with other signals, vocal in speech, or manual in sign. We investigated both of these aspects of integration in a novel pointing elicitation task. Participants viewed brief live-action scenarios and then responded to questions about the locations and objects involved. The questions were designed to elicit utterances in which pointing would serve different semantic functions, sometimes bearing the full load of reference (‘load-bearing points’) and other times sharing this load with lexical resources (‘load-sharing points’). The elicited utterances also provided an opportunity to investigate issues of structural integration. We found that, in both speakers and signers, pointing was produced with greater arm extension when it was load bearing, reflecting a common principle of semantic integration. However, the duration of the points patterned differently in the two groups. Speakers’ points tended to span across words (or even bridge over adjacent utterances), whereas signers’ points tended to slot in between lexical signs. Speakers and signers thus integrate pointing into language according to common principles, but in a way that reflects the differing structural constraints of their language. These results shed light on how language users integrate gradient, less conventionalized elements with those elements that have been the traditional focus of linguistic inquiry.